1994
DOI: 10.1007/bf00572912
|View full text |Cite
|
Sign up to set email alerts
|

Cotrel-Dubousset instrumentation in the treatment of unstable thoracic and lumbar spine fractures

Abstract: The use of computed tomography and developments in spinal biomechanics have led to a better understanding of vertebral fractures. The disappointing results achieved with conservative treatment have led to an increasing popularity of surgical treatment in the last 15 years. The results of 20 unstable thoracic or lumbar spine fractures treated surgically with Cotrel-Dubousset instrumentation at the First Clinic of Orthopaedics and Traumatology of the Ankara Social Security Hospital between December 1988 and June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The current study is one of the largest to our knowledge in the English literature reported on P/TPS in the treatment of FDI of the thoracic spine. Aside from its limitations, our data supports that FDI of the thoracic spine may be amendable to a uniform surgical approach that allows for the reduction and restoration of the posterior tension band with a biomechanically rigid pedicle screw construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The current study is one of the largest to our knowledge in the English literature reported on P/TPS in the treatment of FDI of the thoracic spine. Aside from its limitations, our data supports that FDI of the thoracic spine may be amendable to a uniform surgical approach that allows for the reduction and restoration of the posterior tension band with a biomechanically rigid pedicle screw construct.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data reporting the results of the treatment of purely thoracic (T1-T10) FDI. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Various classification schemes have been devised in an attempt to define the mechanism of injury and treatment guidelines. [20][21][22][23] Denis' 3 column theory describes FDI as a failure of the middle and posterior columns under tension, and a possible failure of the anterior column under compression when the flexion force in association with an axis in the anterior column is generated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Benzer kırıklara koruyucu tedaviden, erken cerrahi tedaviye kadar çok çeşitli tedavi yöntemleri tanımlanmıştır [2]. Son 50 yıldır, vertebra kırıklarında, posterior ve/veya anterior yaklaşımla posterior, anterior veya kombine enstrümantasyon uygulamaları tedavide kullanılmakta olup, her üç seçenek ile elde edilen çok başarılı sonuçlar bildiren çalışmalar yayımlanmıştır [3,4,5,6,7,8,9,10]. Diğer taraftan hala herkesçe kabul edilebilir, geçerliliği ve güvenirliliği kanıtlanmış, bir torakolomber bölge kırık sınıflaması olmaması, cerrahi tedavide en çok başvurulan nörolojik yaralanma üzerinde cerrahi veya konservatif tedavinin benzer değişimlere yol açması, "spinal instabilite" kavramı konusunda hali hazırda bir kesinlik ve netlik olmaması torakolomber bölge kırıklarının tedavisi konusundaki karmaşanın sürmesine yol açmaktadır.…”
Section: Introductionunclassified